Counterterrorism Systems of Spain and Poland: Comparative Studies - Zięba, Aleksandra (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
This paper analyses the counter-terrorism systems in Spain and Poland. This comparative study looks at legal, institutional, and conceptual solutions. In particular, criminal legal regulations and various institutions fighting terrorism are analysed, as are the main goals and tasks of these bodies. The paper shows the scale of terrorist incidents and evolution of terrorist threats in both countries.

W artykule została przeprowadzona analiza porównawcza systemów przeciwdziałania terroryzmowi w Hiszpanii i Polsce. Analiza ta obejmuje poziom prawny, instytucjonalny oraz operacyjny i taktyczny. Dodatkowo ukazano skalę incydentów terrorystycznych w wybranych krajach, celem ukazania skali zagrożenia.
Systemy antyterrorystyczne Hiszpanii i Polski: studium porównawcze
Keywords: terrorism; counterterrorism; Spain; Poland; terroryzm; zwalczanie terroryzmu; Hiszpania; Polska